PANDANGAN TOKOH AGAMA DAN TOKOH MASYARAKAT TERHADAP TRADISI BEGALAN DALAM PERNIKAHAN - Khasanah, Nadirotul; Masruri, Masruri (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
Cultural diversity in Indonesia includes belief systems that are still alive and implemented by the community. Just like in marriage. This research aims to find out the views of religious leaders and community leaders in Tritih Lor village, Jeruk Legi sub-district regarding the begalan tradition procession at weddings and regarding whether or not the begalan tradition is permissible at weddings based on Islamic law. This research is field research, field research is a type of qualitative research where researchers are directly able to obtain the information or data needed. The results of this research are that the begalan tradition begins with the groom's group walking towards the bride's house. In the middle of the journey, thieves were stopped and there was a war of words. It was at this time that the meaning of some of the parabots used was explained. After the mugger breaks the kendil, this is a sign of the end of the begalan tradition procession. If the pillars and conditions have been met, you can carry out traditions that do not violate the rules of the Islamic religion. Like the begalan tradition, the begalan tradition in the implementation process does not conflict with Islamic law. The begalan tradition is not prohibited in Islam because it is not included in shirk or heresy. The begalan tradition is permitted in Islam because the begalan tradition is included in the authentic urf which in the implementation process is not some are contrary to the texts (verses and hadith), do not eliminate benefits, do not bring harm or change what is haram into halal or vice versa.